Concepções de significado: implicações no ensino da matemática na alfabetização - SILVA, Carlos Evaldo dos Santos (Universidade Federal do Pará, 2017)
Discuss the implications of the language design have in teaching mathematics literacy is the goal of this work. For this, we will support the understandings of the meaning of language present in the second philosophy of Ludwig Wittgenstein. In seeking to attribute meaning to the mathematical language we found two perspectives: one understands the language as mere representation of objects in the world, whether real, imaginary or mental, that is, its meaning would be those loved extralinguistic - referential; the other delegates to the language the starring role, considering it as a constituent element of the world, which carries in it its meaning - the pragmatic. It is the latter that dissolves, in our view, the existing confusion in the teaching of mathematics education and that gives us better answers to the problems concerning the significance of knowledge of this discipline. Our empirical research took place with a literacy professor at the Rede Municipal de Educação de Belém times when we have seen his performance in the classroom and in an interview that enabled us to understand their views on language and that confusion would result from them. We note that the reference design is dominant and that three major confusions are present: the first is to assign a rule necessarily a descriptive function; the second is to not consider the various language games that make up the daily life of the classroom; and the last is the call to leave the traditional teaching, based on a supposedly practical "mechanics" and "passive" by a school that provides the "autonomy" of our children, enabling them to be naturally build your knowledge, and devalues mischaracterizes the main function of the teacher who is teaching.